THE ANALYSIS OF PRESUPPOSITION IN “CNN” TWITTER SOCIAL MEDIA: PRAGMATICS APPROACH - Saragi, Christina Natalina; Simarmata, Rina Octavia; Purba, Adiman Juahta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
Good and appropriate presuppositions helped to find the right variety of words before saying something in interaction and communication. Therefore, research on presuppositions is important in the communication and meaning-making of an interaction. By referring to Yule's theory (1996), this study aims to identify the types of pragmatic presuppositions found in comments netizens in the CNN Twitter. The data of this study is taken from the comment’s netizen in CNN Twitter. In collecting the data, the researcher used the observation method. The finding of this research showed that 100 data fulfill all six types of presupposition, that is existential presupposition (17), lexical presupposition (36), factive presupposition (38), structural presupposition (10), counterfactual presupposition (15), and non-factive presupposition (20). The conclusion, this research highlights the importance of pragmatics analysis in understanding netizen comments on social media and their implications for media communication.